BS16 The role of parasympathetic nervous system in the infarct-limiting effect of SGLT2 inhibitors. (4th June 2021) - Basalay, Maryna; Davidson, Sean; Yellon, Derek
Abstract : Introduction: As long-term outcome in patients with acute myocardial infarction (MI) is predicted by final infarct size (IS), reducing IS is of paramount importance. Recent experimental studies have demonstrated a strong infarct-sparing effect of SGLT2 inhibitors – a class of drugs which have proved to be safe and beneficial in patients with heart failure. Repurposing SGLT2 inhibitors for the benefit of patients presenting with an acute MI should be preceded by investigation of the underlying mechanisms of infarct limitation. Experimental and clinical data indicate a potential role for autonomic modulation in these mechanisms, specifically sympatho-inhibition. The aim of this study was to evaluate the role of parasympathetic tone in the infarct-sparing effect of SGLT2 inhibitors. Methods: Twenty seven Sprague Dawley rats were fed with the diet containing the SGLT2 inhibitor Ertugliflozin or vehicle for 3 days. Myocardial ischaemia/reperfusion injury was caused by a 40-min left anterior descending coronary artery occlusion followed by 2 hours of reperfusion under isoflurane anaesthesia (4% for induction and 1.5-2% for maintenance). Two groups of animals, pre-treated with Ertugliflozin, were subjected to parasympathetic denervation prior to myocardial ischaemia, either with the muscarinic receptor antagonist, atropine sulfate i.v. (2 mg/kg bolus, then 1 mg/kg/h), or bilateral cervical vagotomy ( figure 1 ). Results: Pre-treatment with Ertugliflozin reduced IS by 63% (p<0.001). Blocking muscarinic receptors with atropine abolished the infarct-limiting effect of Ertugliflozin (IS=45±2%, p>0.05 vs. vehicle, p<0.001 vs. ertugliflozin), whereas bilateral mechanical vagotomy only attenuated cardioprotection (IS=32±5%, p<0.01 vs vehicle and Ertugliflozin). Conclusion: These results suggest that the Infarct-limiting effect of SGLT2 inhibitor Ertugliflozin may be mediated via M-cholinoreceptors. Conflict of Interest: No